2012
DOI: 10.1016/j.virol.2011.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-rich lipid rafts are required for release of infectious human respiratory syncytial virus particles

Abstract: Cholesterol and sphingolipid enriched lipid raft micro-domains in the plasma membrane play an important role in life-cycle of numerous enveloped viruses. Although human respiratory syncytial virus (RSV) proteins associate with the raft domains of infected cells and rafts are incorporated in RSV virion particles, the functional role of raft during RSV infection was unknown. In the current study we have identified rafts as an essential component of host cell that is required for RSV infection. Treatment of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 52 publications
1
56
0
1
Order By: Relevance
“…Beyond entry, cell membrane cholesterol is also required for the synthesis of several viruses. Cholesterol-enriched lipid rafts in cell membranes play a role in the formation of replication compartments and in the assembly and budding of several enveloped viruses (14)(15)(16)(17)(18)(19)(20)(21). Beyond its role in West Nile virus (WNV) entry, the postentry replication of the WNV infectious strain NY385-99 is independent of cell cholesterol (22).…”
mentioning
confidence: 99%
“…Beyond entry, cell membrane cholesterol is also required for the synthesis of several viruses. Cholesterol-enriched lipid rafts in cell membranes play a role in the formation of replication compartments and in the assembly and budding of several enveloped viruses (14)(15)(16)(17)(18)(19)(20)(21). Beyond its role in West Nile virus (WNV) entry, the postentry replication of the WNV infectious strain NY385-99 is independent of cell cholesterol (22).…”
mentioning
confidence: 99%
“…We also recently reported that RSV utilizes lipid rafts during virus budding (42), and since budding events of several viruses are regulated by Nedd proteins like Nedd4 (Nedd4 is a component of ESCRT [the endosomal sorting complex required for transport] pathway [43,44] that utilizes L (lateassembly) domains during virus budding), we knocked down (via RNA interference [RNAi]) several Nedd proteins, including Nedd4 and Nedd8 (as a control). During those studies, we surpris-ingly uncovered that Nedd8 knockdown drastically reduced IL-1␤ production from RSV-infected cells.…”
mentioning
confidence: 99%
“…3 Cholesterol, an essential component of the plasma membrane, has been implicated in the regulation of membrane fluidity, permeability, and cell surface receptor function. [4][5][6] Because cholesterol contributes to the establishment of a cornified barrier, it plays a crucial role in keratinocytes. Atopic dermatitis has even been shown to occur in parallel with keratinocytes disrupted by lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…It is also an important contributor to cell-cell adhesion, migration, and even endocytosis. [4][5][6][7] However, despite increasing interest in the bronchial epithelium, the possible role of cholesterol in inflammation of the airway or the development of asthma has not been investigated. Among the numerous cytokines and chemokines released from human airways, interleukin-8 (IL-8) is a representative…”
mentioning
confidence: 99%